Analisa Kuantitatif dan Kualitatif Potensi Likuifaksi - Wahyu Budi Kusuma (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2020)
In 2018, precisely on September 28, Indonesia was shocked by the phenomenon of movement and the collapse of everything on the surface in the form of buildings and plants in the Petobo and Balaroa regions, after an earthquake measuring 7.4 on the Richter scale shook Palu, Central Sulawesi. This phenomenon is known as liquefaction. What is the liquefaction? How did it happen? How is the process happening? How to overcome it? The question became a trending topic after the earthquake. This paper is compiled from various sources and opinions of experts in order to answer the questions above.Liquefaction is a natural phenomenon that usually occurs in areas with water-saturated soil conditions, shallow ground water levels and water saturation. Potential liquefaction can be predicted qualitatively and quantitatively. Qualitative analysis is used for regional scales while quantitative analysis is used for detailed scales. The compilation of potential zones of liquefaction can be done using the value of Liquefaction Potential Index (LPI), Liquefaction Severity Index (LSI) and Liquefaction Risk Index (LRI). Common methods for determining liquefaction potential are by calculating the strength of the ground to prevent liquefaction due to earthquake called cyclic resistance ratio (CRR) and shear stress due to earthquake called cyclic stress ratio (CSR). CRR and CSR are calculated from data obtained by conducting a self penetration test (SPT) or cone penetration test (CPT).